Dual Pricing Algorithm in ISO Markets - O'Neill, Richard P.; Castillo, Anya; Eldridge, Brent; Hytowitz, Robin Broder (IEEE transactions on power systems, 2017)
The challenge to create efficient market clearing prices in centralized day-ahead electricity markets arises from inherent nonconvexities in unit commitment problems. When this aspect is ignored, marginal prices may result in economic losses to market participants who are part of the welfare maximizing solution. In this essay, we present an axiomatic approach to efficient prices and cost allocation for a revenue neutral and nonconfiscatory day-ahead market. Current cost allocation practices do not adequately attribute costs based on transparent cost causation criteria. Instead we propose an ex post multipart pricing scheme, which we refer to as the dual pricing algorithm. Our approach can be incorporated into current day-ahead markets without altering the market equilibrium.